EKSTRAK CYMBOPOGON CITRATUS DAN EUGENIA AROMATICUM EFEKTIF UNTUK PENYEMBUHAN GINGIVITIS - Eka Febriani Puspaningrum; Ratnawati Hendari; Rochman Mujayanto (ODONTO : Dental Journal, 2015)
Introduction: Gingivitis is an inflammatory gingiva which has early sign is a little bleeding and mild swelling of the gingiva and if this gingivitis is untreated it could be the periodontitis. The process of gingivitis can be prevented with an antibacterial compound.Purpose: The aim of this research is to determine the effectiveness of topical extracts of lemongrass and clove to cure gingivitis.Methods: This experimental research used post test control group design. The samples were 28 male Wistar rats 2-3 months that were divided into 4 groups. Group I as a positive control was given amoxicillin and metronidazole, group II was given lemongrass extract, group III was given clove extracts, and the fourth group was given a combination of lemongrass and clove extracts. The addition of an extract is done in twice a day for 2 days.Results: Healing of gingivitis seen from the number of polymorphonuclear leukocytes/PMN leukocytes. The mean number of PMN in group I = 5.00, group II = 9.43, group III = 8:57, and group IV = 5.86. Based on the Kruskal Wallis test there was not a significant difference of the PMN number withinfourth experiment group.Conclusion: The conclusion of this study was combination of lemongrass and clove extract had an effectiveness level that almost similar to metronidazole dan amoxicillin in decreasing the number of polymorphonuclear leukocytes in the gingivitis healing process.